NEW DASYCLADAL ALGAE FROM THE ANISIAN (MIDDLE TRIASSIC) OF LIKA (CROATIA) - Tonći Grgasović (Rudarsko-geološko-naftni Zbornik)
Two new species of dasycladal algae are described from the Anisian limestones of the Lika region in Croatia. Griphoporella? speleoluka n. sp. is characterized by very small cylindrical thallus and vesiculiform laterals arranged in close whorls. In consecutive whorls, laterals are positioned one above the other. It differs from other species by smaller dimensions and the arrangement of the laterals. Palaeodasycladus primus n. sp. has cylindrical thallus with whorls of inclined laterals up to the third order. Primary laterals are not completely calcified, producing so-called intusannulation. Trichoform or tubular secondary laterals bear bundles of thin, probably trichoform, tertiary laterals. Both of the new species have been found within typical Anisian microfossil assemblage.